Finding Balance: Academic Leaders that Teach - Tiffani Butler (Academic Chairpersons Conference Proceedings, 2020)
The presenter and participants will discuss multiple approaches to juggling the demands of leading and managing a department, while maintaining teaching responsibilities. We will explore best practices that support chairs as leaders that teach.
Keywords: Leader; Manager; Teacher; Academic Balance